Successful fertility preservation by expectant management of a cervico-isthmic pregnancy with fetal death in the second trimester: A case report - Soichiro Obata; Ryosuke Shindo; Masako Otani; Etsuko Miyagi; Shigeru Aoki (Elsevier, 2023)
In a cervico-isthmic pregnancy, the risk of placenta accreta increases with advancing gestational age. Previous reports have detailed cases that required hysterectomy at delivery or artificial abortion at an early gestational age. However, to the best of our knowledge, there have been no previous reports on the management of a cervico-isthmic pregnancy with fetal death during the second trimester.A 33-year-old primigravid woman was diagnosed with a cervico-isthmic pregnancy and fetal death at 15 weeks of gestation. Placenta accreta was suspected; hence, we chose expectant management and to observe the patient for placental tissue regression. After 5 weeks of expectant management, the ultrasonographic findings suggested remission of placenta accreta. Therefore, we performed a cesarean delivery and terminated the pregnancy. All uterine contents were removed, and the uterus was preserved.In cervico-isthmic pregnancy cases with fetal death, as in the current case, the possibility of fertility preservation could be increased by observing for placental tissue regression through expectant management.